Performance analysis of relay enhanced in LTE-advanced cellular network / Suhada Alias - Alias, Suhada (2015)
Relaying technology was introduced in Long Term Evolution (LTE) Release 10 to enhance coverage and throughput especially at cell edge area. It has been considered as one of feasible solutions for extending the coverage and improving network capacity due to its easy deployment with a comparatively low cost of installation and maintenance. This paper presents the performance of relay involving several scenarios within the LTE network. Each scenario undergone evaluations with several relay deployment environments to determine their performance impact on Symbol Error Rate (SER) and Signal to Noise Ratio (SNR). The evaluations are performed using Matlab simulation which is integrated with the Wireless World Initiative New Radio Phase 2 (WINNER II) channel model. This study has demonstrated enhancement in the network performance by transmitting signal through relay node than conventional transmission. Indirectly, it has also enhanced the spectral efficiency gain and quality of service by increasing the handover success rate and reducing transmission interruption.